Lemmus trimucronatus - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
33. Nearctic Brown Lemming Lemmus trimucronatus French: Lemming brun / German: Brauner Lemming / Spanish: Lemming neartico Other common names: Brown Lemming Taxonomy. Arvicola trimucronata [sic] J. Richardson, 1825, Point Lake, District of Mackenzie, Canada. In the past, L. trimucronatus was synonymized with L. sibiricus. Ten subspecies recognized, but the subspecies chrysogaster may be synonymous with alascensis. Subspecies and Distribution. L.t.trimucronatusJ.Richardson,1825—NYukon,NorthwestTerritories,Nunavut,includingPrinceofWales,Somerset,KingWilliam,Baffin,andSouthamptonIs,andNManitoba(Canada). L.t.alascensisMerriam,1900—NcoastalAlaska. L.t.chrysogasterJ.A.Allen,1903—NWRussianFarEastEtoChukchiPeninsula. L.t.harroldiSwarth,1931—NunivakI(offshoreAlaska). L.t.helvolusJ.Richardson,1828—SYukon,NBritishColumbia,andNWAlberta(Canada). L.t.minusculusOsgood,1904—SWAlaska. L.t.magripesTrue,1894—PribilofIs(offshoreAlaska). L.t.phaiocephalusManning&Macpherson,1958—BanksandVictoriaIs(CanadianArcticArchipelago). L.t.subarcticusBee&Hall,1956—NAlaska. L. t. yukonensis Merriam, 1900 — C & SE Alaska. Descriptive notes. Head-body 115-133 mm, tail 11-18 mm; weight 51-90 g. Males are 1-6% larger than females. Maximum weight recorded in laboratory reared individuals is 131-4 g. The Nearctic Brown Lemming is slightly smaller than the Siberian Brown Lemming (L. sibiricus) but has similar body proportions. Females have four pairs of nipples. Pelage is monochromatic, and spinal streak is occasionally retained on front of head but always absent from back. Dorsal fur is brownish gray, posteriorly with rusty shades; flanks are buffy or ocherous; and underparts are gray-washed buff. Winter fur is lighter. Melanistic and albino individuals have been reported in the wild. Skull and molar pattern are similar to those of the Norway Brown Lemming (L. lemmus). Habitat. High Arctic tundra with freezing temperatures for at least eight months of the year. In Alaska, Nearctic Brown Lemmings were recorded up to elevations of 1500 m. ...